Code compliance for advanced technology facilities a comprehensive guide for semiconductor and other hazardous occupancies - Acorn, William R. (Materials science and process technology series., 1993)
Facilities that utilize hazardous liquids and gases represent a significant potential liability to the owner, operator, and general public in terms of personnel safety and preservation of assets. A catastrophic incident or loss of property or personnel is to be avoided at all costs. This book was conceived to give the reader a guide to understanding the requirements of the various codes and regulations that apply to the design, construction, and operation of facilities utilizing hazardous materials in their processes.